1998
DOI: 10.1046/j.1365-2435.1998.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of bee‐flies to the shape and pattern of model flowers: implications for floral evolution in a Mediterranean herb

Abstract: 1. The functional significance of floral traits in Linum pubescens (Linaceae), a Mediterranean annual that is pollinated almost exclusively by the bee‐fly Usia bicolor (Bombyliidae), was investigated. The flies feed on both pollen and nectar, and use the flowers as mating rendezvous sites in the afternoon. 2. Choice experiments with model flowers were used to determine the response of U. bicolor to visual cues, such as shape, size, colour and pattern. 3. Bee‐flies strongly preferred models with a dissected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 29 publications
14
94
0
Order By: Relevance
“…This shortened NDT on radiating flowers in preference tests is similar to the results of previous studies where flower to flower flight times and pollinator search times were lower on flowers with guides than plain flowers (Waser and Price 1985;Leonard and Papaj 2011). Our results are also consistent with Johnson and Dafni (1998), in which bombyliid flies (Usia bicolor) landing on model flowers with radiating lines walked directly towards the point where the lines converged. The reduced NDTs on artificial flowers comprised of radiating lines which lead to the nectary over 'disjunct' guides where radiating lines lead away from the nectary in Goodale et al (2014) is also reminiscent of our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This shortened NDT on radiating flowers in preference tests is similar to the results of previous studies where flower to flower flight times and pollinator search times were lower on flowers with guides than plain flowers (Waser and Price 1985;Leonard and Papaj 2011). Our results are also consistent with Johnson and Dafni (1998), in which bombyliid flies (Usia bicolor) landing on model flowers with radiating lines walked directly towards the point where the lines converged. The reduced NDTs on artificial flowers comprised of radiating lines which lead to the nectary over 'disjunct' guides where radiating lines lead away from the nectary in Goodale et al (2014) is also reminiscent of our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found radiating elements to be more attractive to bees than plain or circular elements (Free 1970;Lehrer et al 1995;Shang et al 2011), while others have shown no preference for artificial flowers with radiating patterns over plain flowers in bee-flies Usia bicolor (Johnson and Dafni 1998). It is possible that the lack of preference observed in this study is related to the fact that the greens used for the background and guide were intentionally similar in order to limit bees positioning themselves close to the nectaries when landing (Lunau et al 2006).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Sprengel (Sprengel, 1793) introduced the concept of nectar guides as floral features that could be used by pollinators to visually locate the nectar. Subsequent experiments revealed that the diurnal hawkmoth Macroglossum stellatarum (Knoll, 1922), bumblebees (Manning, 1956;Kugler, 1966), honeybees (Daumer, 1958;Free, 1979) and bee-flies (Johnson and Dafni, 1998), among other insects, successfully utilize visual nectar guides. Here we show that the utility of Spengel's idea extends beyond the visual system, as the tactile sensitivity of the proboscis of M. sexta allows these moths to exploit the physical features of flowers in order to find nectar (Figs·3,5,6).…”
Section: Vision and Mechanoreception During Flower Probingmentioning
confidence: 99%
“…In Dorset, all five plants received close to or above 90% bee visits. In Israel, 19 of the 23 plants had over 60% of their visits from bees (many of these bee-specialists with over 90% bee visits, and Nonea, Phlomis and Prasium with 100%), whilst Convolvulus, Ornithogalum and Tordylium received around 40% bee visits and Linum (a known bombyliid specialist (Johnson and Dafni 1998)) had none. In Kenya, 10 out of the 19 plants had over 60% bee visits (only three, Chlorophytum, Commelina and Hypoestes, recording over 90%), whilst seven received less than 20% bees.…”
Section: Resultsmentioning
confidence: 99%